The galactose elimination capacity test to monitor liver disease course in patients with Wilson's disease. (4th May 2022) - Munk, Ditte Emilie; Björklund, Jessica; Lund Laursen, Tea; Vilstrup, Hendrik; Ott, Peter; Grønbæk, Henning; Damgaard Sandahl, Thomas
Abstract: Background: The prognosis of Wilson's disease (WD) has changed radically since the introduction of medical therapy with chelators and zinc. However, there is an unmet need for methods to evaluate the long-term treatment response and the liver disease progression in order to identify treatment failures. The galactose elimination capacity test (GEC) is a physiological measure of the total metabolic capacity of the liver, and a strong predictor of long- and short-term mortality in patients with liver cirrhosis. Our aim was to investigate if the GEC test is useful for evaluation of treatment response and prediction of treatment failures in WD patients. Methods: We included all patients with WD in Denmark from 1992 through 2017 and retrieved data on GEC along with data on transplantation and death. Results: In total, 37 patients had completed one or more GEC tests. Of these, 31 were alive (three transplanted) and six were dead (two transplanted). A total of 24 patients had completed more than one GEC test. All 18 alive, nontransplanted patients showed improvement in GEC values following onset of treatment, except one patient, who was clinically confirmed with treatment failure. All six patients who underwent liver transplantation or died had a prior decline in their GEC. The difference in GEC development between patients alive and not transplanted and patients dead or transplanted was significant ( p  < .001). Index GEC values could not predict transplantation or death ( p  = .26). Conclusion: The GEC test is a promising tool for monitoring treatment response and identifying treatment failures in patients with WD.